Ethnobotanical survey of medicinal plants with antifungal activities in Makhado Local Municipality, Limpopo Province, South Africa - Machaba, Tambudzani Caroline (My University, 2018)
The aim of the study was to investigate medicinal plants used for the treatment of various ailments by the traditional healers and local people and to determine antifungal activities against animal fungal pathogens. Ethnobotanical survey was conducted to identify medicinal plants used by local people and traditional healers to treat various ailments in Makhado Local Municipality, Vhembe District, Limpopo, South Africa. A questionnaire was designed to gather information on the local name of plants, plant parts used and the methods of preparation and administration by the traditional healers. In our findings, sixty-three medicinal plants belonging to thirty-three families were identified to be used for treatment of various diseases such as chest complaint, sexual transmitted infections, headache, swollen legs, hypertension, blood purification, asthma, and infertility. Specific parts of the plant used for medicinal purposes vary from species to species and from one traditional healer to another. The dominant families were Fabaceae, Celastraceae and Euphorbiaceae. Of the sixty-three plants species identified, trees were the most predominant plant form (53%), followed by shrubs (23%), herbs (14%), and climbers (10%). Root, fruit, bark, leaves, seeds and in some instances the whole plant are used for the preparation of medicine while decoction and infusion were the general methods of preparation. The mode of administration of medicine was mainly oral. The most frequently used plant species were Warbugia salutaris (Bertol.f.) Chiov, Sclerocarya birrea (A.Rich) Hochst and Eleondron transvaalense (Burtt Davy) R.H. Archer. Eight plant species (Asparagus buchananii Bak., Albuca seineri (Engl. & K.Krause) J.C Manning & Goldblatt, Elephantorrhiza elephantina (Burch.) Skeels, Indigofera circinnata Benth, Maerua juncea Pax, Pentarrhinum insipidum E. Mey., Senna italica Mill. and Schinus molle L.) were selected based on the information given by the local people and the traditional healers for further phytochemical analysis and microbiological assays. Antifungal activities of the selected plant species were determined against three fungal pathogens namely, Candida albicans, Cryptococcus neoformans and Aspergillus fumigatus. Of the tested plant species, hexane leaf extracts of M. juncea, ethyl acetate leaf extracts of S. italica, A. buchananii and E. elephantina were the most active against Candida albicans, Cryptococcus v neoformans and Aspergillus fumigatus with Minimum inhibitory concentration (MIC) values ranging between 0.02 mg/ml and 0.08 mg/ml. Bioautography assay was used to determine the number of active compounds in the plant extracts. No active compounds were observed in some plant extracts against the tested animal fungal pathogens indicating possible synergism. The most promising plant species were: A. buchananii, A. seineri and M. juncea, all had shown good activity with 4 compounds against A. fumigatus. Acetone and methanol extracts had the same active compounds visible on bioautograms. Most of the active compounds were observed in TLC chromatograms developed Benzene: ethanol: ammonia hydroxide (BEA) eluent solvent system. Based on excellent antifungal activity against the tested microorganisms, leaf extracts of A. buchananii, A. seineri M. juncea, P. insipidum and root extracts of I. circinnata were also tested for cytotoxicity against the Vero kidney cells. All plant extracts investigated were relatively not toxic against the cells with LC50 ranging between 0.131 mg/ml and  1 mg/ml. Water extracts of A. buchananii, A. seineri and M. juncea had LC50  1 mg/ml. The leaf aqueous extracts of P. insipidum were less toxic than root aqueous extracts of I. circinnata with LC50 of 0.65 mg/ml and 0.49 mg/ml against the Vero kidney cells respectively. The results indicate that the local people and traditional healers in Makhado Local Municipality use medicinal plants and their indigenous knowledge on the treatment of fungal infections and related ailments.
Thesis (M. Sc. (Botany)) -- University of Limpopo, 2018
Keywords: Ethnobotanical survey; Medicinal plants; Antifungal activities; Makhado Local Municipality; South Africa; Medicinal plants -- South Africa; Ethnobotany; Antifungal agents; Healers